Callus Induction and Plant Regeneration from Carum copticum and Assessment of Antioxidant Responses and Phytochemical Profiling by In Vitro Salinity Stress - Roya Razavizadeh; Fatemeh Adabavazeh; Marzieh Rezaee Chermahini; Setsuko Komatsu (Horticulturae, 2022)
Higher production of secondary metabolites is one of the adaptive responses to alleviate the impact of environmental injuries. In the present investigation, the production of these metabolites with medicinal importance induced by salinity in Carum copticum was investigated. To develop a better way for the production of medicinal substances, callogenesis and plant regeneration were analyzed, and seeds, calli, and/or regenerated seedlings were exposed to different concentrations of NaCl under in vitro culture conditions. The maximum frequency of callus induction was obtained on a medium supplemented with 0.25 mg L−1 2, 4-dichlorophenoxyacetic (2,4-D) and 1 mg L−1 benzyl amino purine (BAP) from stem explants. Plant regeneration with multiple shoots was obtained from pieces of callus transferred to MS medium fortified with 0.25 mg L−1 2,4-D and 1.5 mg L−1 BAP. Four weeks after treatment, salinity induced a substantial increase in the accumulation of reducing sugars and proline as compatible osmolytes and the activity of antioxidant enzymes. Total phenolics and anthocyanin significantly increased in all samples with increasing NaCl concentrations; however, the regenerated seedlings showed a reduction in these compounds at severe NaCl concentration compared to the control. Moreover, NaCl enhanced thymol, γ-terpinene, sabinene, and myrcene in the seedlings and calli, as well as carvacrol, limonene, and α-terpinene in the regenerated seedlings. These results suggest that salinity has a marked impact on improving the content of antioxidant metabolites and essential oils in C. copticum, whose callus might be the most salt tolerant in all tested samples.